THE PROFESSIONAL PERSONALITY PROFILE FROM THE PERSPECTIVE OF THE SOCIAL INTELLIGENCE OF THE STUDENTS - Paladi Oxana; Ilicciev Maxim (International Journal of Innovative Technologies in Social Science, 2023)
The article presents the author’s conceptions regarding the particularities of student’s social intelligence from the perspective of the professional personality profile; some results are presented in the research carried out with reference to the impact of social intelligence on the professional personality profile of students. Both levels of manifestation of social intelligence and personality profiles for students involved in vocational training in the context of an occupational area are briefly presented. At the same time, is described the relationship between social intelligence and personality profile for determining the extent to which social intelligence influences the formation of student’s professional personality profile. The basic objective of the research was focused on highlighting the relationship between social intelligence and professional personality profile, which led to the outline of a definition of social intelligence from the perspective of the professional personality profile. At the same time, following the obtained experimental results, we propose an integrative model of the formation of the professional personality profile from the perspective of social intelligence.